Toward 3D Integration of 1D Conductors: Junctions of InAs Nanowires. (25th October 2011) - Wu, Phillip M.; Samuelson, Lars; Linke, Heiner
Abstract : A vision and one of the next challenges in nanoelectronics is the 3D integration of nanowire building blocks. Here we show that capillary forces associated with a liquid-air meniscus between two nanowires provides a simple, controllable technique to bend vertical nanowires into designed, interconnected assemblies. We characterize the electric nature of the junctions between crossed nanowires in a lateral geometry, which is one type of basic unit that can be found in interconnected-bent vertical nanowires. The crossed nanowire junction is capacitive in nature, and we demonstrate that one nanowire can be used to field effect gate the other nanowire, allowing for the possibility to develop extremely narrow conducting channels in nanowire planar or 3D electronic devices.